The self and its emotions - Kristjánsson, Kristján, 1959- (Studies in emotion and social interaction., 2010)
"If there is one value that seems beyond reproach in modernity, it is that of the self and the terms that cluster around it, such as self-esteem, self-confidence, and self-respect. It is not clear, however, that all those who invoke the self really know what they are talking about, or that they are all talking about the same thing. What is this thing called 'self', then, and what is its psychological, philosophical, and educational salience? More specifically, what role do emotions play in the creation and constitution of the self? This book proposes a realist, emotion-grounded conception of selfhood. In arguing for a closer link between selfhood and emotion than has been previously suggested, the author critically explores and integrates self research from diverse academic fields. This is a provocative book that should excite anyone interested in cutting-edge research on self issues and emotions that lies at the intersection of psychology, philosophy of mind, moral philosophy, and moral education."--Jacket.